Nutritional status and life quality in patients undergoing bariatric surgery - SILVA,Paulo Roberto Bezerra da (2014)
BACKGROUND: The obesity has achieved an alarming increase in recent years, which led this disease to global epidemic condition. AIM: To evaluate the nutritional status as well as the quality of life of obese patients undergoing bariatric surgery. METHODS: A transversal study was conducted with obese adults of both genders who underwent bariatric surgery by Fobi-Capella technique for at least 30 days. It was evaluated: age, gender, marital status, occupation, weight before surgery, current weight, height, preoperative and current BMI, weight loss and loss of excess weight percentages, presence of clinical manifestations and food intolerances. RESULTS: The sample consisted of 70 patients, being 81.4% female, 37.1% aged 30 to 39 years, 58.6% were married, 41.4% have undergone the bariatric surgery in the last 12 months. It was observed a reduction in BMI from 37.2 kg/m2 (one to three months) to 28.9 kg/m2 (>12 months) and consequent increase in weight loss and loss of excess weight percentages. The most frequent clinical manifestation was alopecia (62.9%). The most reported food intolerance was on the red meat (24%). According to the Baros questionnaire, 50% of patients were classified as having good quality of life. CONCLUSION: The operation of Fobi-Capella proved to be effective in promoting gradual and lasting weight loss. Quality of life was considered good in most patients, indicating that the operation had a positive impact on their lives.